Synthesis and selected transformations of 2-unsubstituted 1-(adamantyloxy)imidazole 3-oxides: straightforward access to non-symmetric 1,3-dialkoxyimidazolium salts - Mlostoń, Grzegorz; Celeda, Małgorzata; Urbaniak, Katarzyna; Jasiński, Marcin; Bakhonsky, Vladyslav; Schreiner, Peter R.; Heimgartner, Heinz (Beilstein Journal of Organic Chemistry, 2019)
Adamantyloxyamine reacts with formaldehyde to give N-(adamantyloxy)formaldimine as a room-temperature-stable compound that exists in solution in monomeric form. This product was used for reactions with α-hydroxyiminoketones leading to a new class of 2-unsubstituted imidazole 3-oxides bearing the adamantyloxy substituent at N(1). Their reactions with 2,2,4,4-tetramethylcyclobutane-1,3-dithione or with acetic acid anhydride occurred analogously to those of 1-alkylimidazole 3-oxides to give imidazol-2-thiones and imidazol-2-ones, respectively. Treatment of 1-(adamantyloxy)imidazole 3-oxides with Raney-Ni afforded the corresponding imidazole derivatives without cleavage of the N(1)–O bond. Finally, the O-alkylation reactions of the new imidazole N-oxides with 1-bromopentane or 1-bromododecane open access to diversely substituted, non-symmetric 1,3-dialkoxyimidazolium salts. Adamantyloxyamine reacts with glyoxal and formaldehyde in the presence of hydrobromic acid yielding symmetric 1,3-di(adamantyloxy)-1H-imidazolium bromide in good yield. Deprotonation of the latter with triethylamine in the presence of elemental sulfur allows the in situ generation of the corresponding imidazol-2-ylidene, which traps elemental sulfur yielding a 1,3-dihydro-2H-imidazole-2-thione as the final product.
Keywords: alkoxyamines; imidazole N-oxides; imidazolium salts; nucleophilic carbenes; sulfur transfer reaction

(untitled) - Lettau, H. (Z. Chem., 1970)

(untitled) - Nikitina, G. V.; Pevzner, M. S. (Chem. Heterocycl. Compd., 1993)

(untitled) - Nikitina, P. A.; Perevalov, V. P. (Chem. Heterocycl. Compd., 2017)

(untitled) - Begtrup, M. (Adv. Heterocycl. Chem., 2012)

(untitled) - Wang, Y.; Zhang, L. (Synthesis, 2015)

(untitled) - Mlostoń, G.; Jasiński, M.; Wróblewska, A.; Heimgartner, H. (Curr. Org. Chem., 2016)

(untitled) - Mlostoń, G.; Jasiński, M. (ARKIVOC, 2011)

(untitled) - Mlostoń, G.; Jasiński, M.; Linden, A.; Heimgartner, H. (Helv. Chim. Acta, 2006)

(untitled) - Loska, R.; Mąkosza, M. (Chem. – Eur. J., 2008)

(untitled) - Mlostoń, G.; Jasiński, M.; Heimgartner, H. (Eur. J. Org. Chem., 2011)

(untitled) - Mlostoń, G.; Gendek, T.; Heimgartner, H. (Tetrahedron, 2000)

(untitled) - Ferguson, I. J.; Schofield, K. (J. Chem. Soc., Perkin Trans. 1, 1975)

(untitled) - Mlostoń, G.; Gendek, T.; Heimgartner, H. (Helv. Chim. Acta, 1998)

(untitled) - Mlostoń, G.; Celeda, M.; Prakash, G. K. S.; Olah, G. A.; Heimgartner, H. (Helv. Chim. Acta, 2000)

(untitled) - Laus, G.; Schwärzler, A.; Bentivoglio, G.; Hummel, M.; Kahlenberg, V.; Wurst, K.; Kristeva, E.; Schütz, J.; Kopacka, H.; Kreutz, C.; Bonn, G.; Andriyko, Y.; et al. (Z. Naturforsch., B: J. Chem. Sci., 2008)

(untitled) - Mlostoń, G.; Romański, J.; Jasiński, M.; Heimgartner, H. (Tetrahedron: Asymmetry, 2009)

(untitled) - Mucha, P.; Mlostoń, G.; Jasiński, M.; Linden, A.; Heimgartner, H. (Tetrahedron: Asymmetry, 2008)

(untitled) - Bartz, S.; Blumenröder, B.; Kern, A.; Fleckenstein, J.; Frohnapfel, S.; Schatz, J.; Wagner, A. (Z. Naturforsch., B: J. Chem. Sci., 2009)

(untitled) - Price, S. A.; Manolis, P.; McHale, D.; Green, J. (Br. J. Pharmacol. Chemother., 1960)

(untitled) - Mavunkel, B. J.; Rzeszotarski, W. J.; Kaplita, P. V.; DeHaven-Hudkins, D. L. (Eur. J. Med. Chem., 1994)

(untitled) - Audran, G.; Brémond, P.; Marque, S. R. A. (Chem. Commun., 2014)

(untitled) - Laufer, S.; Hauser, D.; Stegmiller, T.; Bracht, C.; Ruff, K.; Schattel, V.; Albrecht, W.; Koch, P. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Muth, F.; Günther, M.; Bauer, S. M.; Döring, E.; Fischer, S.; Maier, J.; Drückes, P.; Köppler, J.; Trappe, J.; Rothbauer, U.; Koch, P.; Laufer, S. A. (J. Med. Chem., 2015)

(untitled) - Arduengo, A. J.; Harlow, R. L.; Kline, M. (J. Am. Chem. Soc., 1991)

(untitled) - Arduengo, A. J.; Dias, H. V. R.; Harlow, R. L.; Kline, M. (J. Am. Chem. Soc., 1992)

(untitled) - Jochriem, M.; Kirchler, C. G.; Laus, G.; Wurst, K.; Kopacka, H.; Müller, T.; Schottenberger, H. (Z. Naturforsch., B: J. Chem. Sci., 2017)

(untitled) - Wanka, L.; Iqbal, K.; Schreiner, P. R. (Chem. Rev., 2013)

(untitled) - Butov, G. M.; Mokhov, V. M. (Russ. J. Org. Chem., 2014)

(untitled) - Tarazanov, S. V.; Shakun, V. A.; Nesterova, T. N.; Sarkisova, V. S.; Naumkin, P. V.; Nesterov, I. A.; Repina, O. V. (Pet. Chem., 2018)

U.S. Patent - Pilgrim, W. R.; Lagiere, J. (Process for the preparation of 1-adamantane derivatives, 1991)

(untitled) - Raenko, G. F.; Korotkikh, N. I.; Pekhtereva, T. M.; Shvaika, O. P. (Russ. J. Org. Chem., 2001)

(untitled) - Laus, G.; Wurst, K.; Kahlenberg, V.; Kopacka, H.; Kreutz, C.; Schottenberger, H. (Z. Naturforsch., B: J. Chem. Sci., 2010)

(untitled) - Jin, W.; Chen, X.; Dai, P.; Yu, L. (Phytochem. Lett., 2016)

(untitled) - Möhrle, H.; Scharf, U.; Rühmann, E.; Schmid, R. (Arch. Pharm. (Weinheim, Ger.), 1983)

(untitled) - Claisen, L.; Manasse, O. (Ber. Dtsch. Chem. Ges., 1898)

(untitled) - He, Y.; Xue, H.; Zhang, W.; Wang, L.; Xiang, G.; Li, L.; Shang, X. (J. Organomet. Chem., 2017)

(untitled) - Elam, E. U.; Davis, H. E. (J. Org. Chem., 1967)

(untitled) - Creary, X.; Wang, Y.-X. (J. Org. Chem., 1992)